“Paradigms of AI Programming” in Python - Connelly, Daniel; Goel, Ashok (Proceedings of the AAAI Conference on Artificial Intelligence, 2013)
Norvig’s (1992) Paradigms of AI Programming is an important book for learning about AI programming. However, the book uses Common Lisp as the programming language, which is less popular now than in 1992. Thus, we have translated many classical AI programs described in the book into Python, a more commonly used language. We have also documented the programs and offered them as a resource in a course on knowledge-based AI.